PEMAHAMAN MAHASISWA TERHADAP STATISTIKA DALAM MENDUKUNG LITERASI DATA DAN PENGAMBILAN KEPUTUSAN DI ERA DIGITAL - I Wayan Yudik Pradnyana; I Wayan Ady Juliantara; Ida Ayu Mas Agung Prama Iswari (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2026)
Understanding statistics is a crucial competency for students in the digital age, particularly in supporting data literacy and data-driven decision-making. However, various studies have shown that students still experience difficulties in understanding statistical concepts and applying them in real-world contexts. This study aims to comprehensively examine students' understanding of statistics in relation to data literacy and decision-making in the digital age. The Systematic Literature Review (SLR) method was used, analyzing various scientific articles published between 2021 and 2025 from reputable databases. The study results indicate that students tend to experience difficulties in understanding basic statistical concepts, interpreting data analysis results, and connecting them to decision-making. Furthermore, students' data literacy remains relatively low, particularly in the aspects of critical data evaluation and utilization. The findings also indicate a gap between statistical analysis skills and data-driven decision-making. Although the use of technology can facilitate the learning process, its effectiveness is highly dependent on a solid understanding of fundamental concepts. Therefore, innovation in statistics learning is needed through a more contextual, applicable, and integrated approach with data literacy. This research is expected to contribute to the development of more effective statistics learning strategies in the digital age.